2010
DOI: 10.1136/emj.2009.083162
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of naloxone in the management of postseizure complaints of tramadol intoxicated patients: a self-controlled study

Abstract: Naloxone can be considered in the management of postseizure complaints of tramadol toxicity, but further rigorous studies are needed to provide sufficient evidence to support its routine use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 9 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…One randomized controlled study suggested that one single intravenous (IV) 0.8-mg dose of naloxone was responsible for seizurogenic effects in tramadol-overdosed patients [14]. By contrast, another self-controlled study concluded to the efficacy and safety of 0.05 mg naloxone administered IV every 3-5 min after initial resuscitation to manage tramadol-intoxicated patients with postseizure complaints [15]. In addition, tramadol-poisoned children are at risk of apnea and seizures highlighting the necessity to define an efficient and safe antidote to reverse central nervous system (CNS) toxicity, considering the European advice for the treatment of moderate pain in children suggesting limited codeine use and rather tramadol prescription [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…One randomized controlled study suggested that one single intravenous (IV) 0.8-mg dose of naloxone was responsible for seizurogenic effects in tramadol-overdosed patients [14]. By contrast, another self-controlled study concluded to the efficacy and safety of 0.05 mg naloxone administered IV every 3-5 min after initial resuscitation to manage tramadol-intoxicated patients with postseizure complaints [15]. In addition, tramadol-poisoned children are at risk of apnea and seizures highlighting the necessity to define an efficient and safe antidote to reverse central nervous system (CNS) toxicity, considering the European advice for the treatment of moderate pain in children suggesting limited codeine use and rather tramadol prescription [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…14 In Saidi et al, 43 out of 47 patients over 16 years of age had clinical cerebral state monitor benefits after a naloxone injection. 15 Side effects were minor in this study.…”
Section: Discussionmentioning
confidence: 59%
“…This study also reported a case of seizure in one patient, immediately after administering naloxone, although the seizure could be the residual effect of Tramadol. In Saidi et al [22], 43 out of 47 patients over 16 years of age had clinical Cerebral State Monitor benefits after a Naloxone injection. Side effects were minor in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Central nervous system depression and hypoventilation can be treated with Naloxone, which accelerates recovery [22]. Some cases of children intoxicated report the use of Naloxone as a diagnosis and treatment with success [10].…”
Section: Discussionmentioning
confidence: 99%